Integrating Circular Economy Principles into the Energy Finance System to Enhance Sustainability - Iman Supriadi; Eva Wany; Ade Irma Suryani Lating (Universitas Pendidikan Ganesha, 2025)
This research aims to explore and integrate circular economy principles into the energy finance system to improve sustainability. The focus of the research is to analyze how circular economy principles can be adopted in the context of energy finance and evaluate their impact on economic and environmental sustainability. This research utilizes a mixed method approach that combines quantitative and qualitative analysis. For quantitative analysis, time series regression with Error Correction Model (ECM) was used to assess the long and short-term relationship between circular economy dimensions and final energy consumption per capita. Meanwhile, qualitative analysis was conducted through case studies and literature review to identify models and strategies that support the transition to circular economy in the energy finance system. The results show that the integration of the circular economy in the energy finance system has a simultaneous significant effect in the long run on final energy consumption per capita, although this effect is not significant in the short run. The qualitative case study also reveals that adaptive business models and strong policy support are critical for a successful transition to a circular economy in the energy sector. This research makes an important contribution to the sustainability literature by introducing a framework that incorporates circular economy principles into the energy finance system. In addition, this research provides strategic recommendations for policymakers and industry in accelerating the transition to energy sustainability.